Philosophy of Religion in the Twenty-First Century
XVII, 308 p.
Keywords: This book offers the rare opportunity to assess, within a single volume, the leading schools of thought in contemporary philosophy of religion. Their exponents seek to meet objections made to their point of view and to relate it to the other schools represented. Further discussions between adherents of the different schools make it an ideal text for assessing the deep proximities and divisions which characterize contemporary philosophy of religion. The schools of thought represented are: Philosophical Theism, Reformed Epistemology, Wittgensteinianism, Postmodernism, Critical Theory and Process Thought.